The Influence of Maternal Sense of Coherence on 15-year-old Adolescent's Oral Health Outcomes: A Cross-sectional Analysis - Sonali Saha; Sushant Mohanty (Journal of South Asian Association of Pediatric Dentistry)
Aim and background: Salutogenesis emphasizes the origin of health rather than disease. Its core concept, the sense of coherence (SOC), explains how individuals manage stressors to maintain their health. Prior studies have linked maternal SOC with children's oral health behaviors; however, evidence regarding its influence on adolescents’ oral hygiene status is inconsistent. This study explored the relationship between maternal SOC and the oral health status of 15-year-old adolescent children, addressing the gaps in existing research. Materials and methods: This cross-sectional study was conducted from March 2023 to July 2024 among 723 mother–adolescent dyads recruited from urban to semiurban schools. Maternal SOC was assessed using the 13-item Antonovsky SOC scale, encompassing comprehensibility, manageability, and meaningfulness. Adolescents’ oral health was evaluated using the decayed, missing, and filled teeth (DMFT) scores, plaque index, caries severity index, bleeding on probing, and self-assessment of oral health and appearance. Data were collected through questionnaires administered in schools and analyzed using the Statistical Package for the Social Sciences (SPSS) software. Chi-square tests and multinomial logistic regression were used to assess the association between maternal SOC and adolescents’ oral health outcomes. Results: Most mothers (50.48%) exhibited moderate SOC, while 26.28% had high SOC. Adolescents with mothers with high SOC had significantly better oral health outcomes, including lower DMFT scores (p = 0.034), reduced plaque index (p = 0.011), and less severe caries (p = 0.031). High maternal SOC was associated with better self-rated dental health (p = 0.041) and higher satisfaction with self-appearance (p = 0.001). No significant associations were found for bleeding on probing (p = 0.610) or caries in the second molar (p = 0.843). Conclusion: Maternal SOC is a significant determinant of adolescents’ oral health, influencing both objective outcomes and subjective self-assessment. Mothers with high SOC foster healthier behaviors, improved dental health, and positive self-perception in their children. Public health strategies should focus on enhancing maternal SOC through educational initiatives, stress management, and community support. Longitudinal studies are needed to explore the causal pathways and expand the findings across diverse populations. Empowering mothers can yield lasting benefits for family health and well-being. Clinical significance: Enhancing maternal SOC through targeted initiatives—such as community education programs, stress management strategies, and family counseling—enables dental professionals to positively impact adolescent oral health.